Children perception of inter-parental conflicts and their cognitive emotion regulation - Butt, Muhammad Mussaffa (International digital organization for scientific information (IDOSI), 2014)
Basic aim of the present study is to explore the effect of inter-parental conflicts on the cognitive emotion regulation of children, based upon their own perception of these conflicts. Convenient sampling has been used to collect data from children age 9-12 years (50 boys and 50 girls) from different areas of Lahore city.For this study, two scales (CPIC and CERQ-k) are used.These scales are translated into Urdu by the researchers themselves.The results of this study suggest that cognitive emotional regulation emerges as significant predictor, =.35, t =.19, p <.00. The outcomes of the study also indicate that gender and SES have significant effect F (2, 99) = 8.38, p <.00 on CERQ-k.It has been observed that girls have no significant effect on children perception of inter-parental conflicts as p >.06 and R is.06, whereas boys have significant effect as p <.00. The 2 results also indicate that there is significant effect of CERQ-k t (98) = 2.69, p <.00.It has been illustrated that high level of interpersonal conflicts among parents may also lead their children and people related to them towards clinical pathologist that may be dangerous for their future lives.Furthermore, the study concludes that socio-economic statuses also have significant effect on the perception of children during conflicts.The results are discussed in the particular cultural context of Pakistan.